The physiology of the kidney and body fluids - Sukhomlinova, I.E.; Tichonovskay, M.A.; Kirsanova, E.V.; Yeryomina, A.K.; Сухомлінова, Ірина Євгенівна; Тихоновська, Марина Анатоліївна; Кірсанова, Олена Валентинівна; Єрьоміна, Алла Кузьмівна (Zaporizhzhia state medical university, 2016)
Methodical instructions recommended for the students of “General Medicine” specialty who study Physiology. This educational manual contains theoretic materials, the approximate lists of questions to check quality of study. Instructions allows students to acquaint with main definitions of the course “Normal Physiology” and gives a wide list of literature sources for better understanding Normal Physiology during students independent work.
Фізико-хімічні властивості нирок та рідин організму